2019
DOI: 10.1002/ptr.6349
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and safety of chamomile for state anxiety, generalized anxiety disorder, insomnia, and sleep quality: A systematic review and meta‐analysis of randomized trials and quasi‐randomized trials

Abstract: This systematic review and meta‐analysis aimed to study the efficacy and safety of chamomile for the treatment of state anxiety, generalized anxiety disorders (GADs), sleep quality, and insomnia in human. Eleven databases including PubMed, Science Direct, Cochrane Central, and Scopus were searched to retrieve relevant randomized control trials (RCTs), and 12 RCTs were included. Random effect meta‐analysis was performed by meta package of R statistical software version 3.4.3 and RevMan version 5.3. Our meta‐ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 43 publications
(81 reference statements)
0
15
0
2
Order By: Relevance
“…Nutrients 2021, 13, x FOR PEER REVIEW 13 of 24 livering green tea, curcumin, saffron, chamomile, and soy also reported anti-anxiety effects. Meta-analyses of experimental studies using chamomile [50], saffron [51], and curcumin [52,53] found a decrease in anxiety symptoms, while the meta-analysis of studies administering resveratrol reporting a non-significant improvement [54]. A small number of the human experimental studies involved participants with anxiety disorders including three studies using chamomile [55][56][57], two using saffron [58,59], one using curcumin [60], and one using l-theanine [61].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Nutrients 2021, 13, x FOR PEER REVIEW 13 of 24 livering green tea, curcumin, saffron, chamomile, and soy also reported anti-anxiety effects. Meta-analyses of experimental studies using chamomile [50], saffron [51], and curcumin [52,53] found a decrease in anxiety symptoms, while the meta-analysis of studies administering resveratrol reporting a non-significant improvement [54]. A small number of the human experimental studies involved participants with anxiety disorders including three studies using chamomile [55][56][57], two using saffron [58,59], one using curcumin [60], and one using l-theanine [61].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Ancak dört hafta sonunda yapılan ölçümlerde uyku kalitesindeki iyileşme gözlenmemiştir 38 . Literatürde papatyanın kısa vadede uyku kalitesini iyileştirmede güvenli bir yöntem olduğunu belirten bir meta-analiz çalışması bulunmaktadır 39 . Akupres, vücuttaki belirli noktalara basıncın uygulandığı geleneksel bir yöntemdir 40 .…”
Section: Discussionunclassified
“…Sparse or no scientific data were found to support the efficacy of most products as hypnotics, including chamomile, hop (alone), hawthorn, St. John's wort, and rosemary. Notably, one recently published systematic review and a meta-analysis indicated chamomile as efficacious and safe for improving sleep quality and generalized anxiety disorders but highlighted scarce effect for insomnia [67,68]. Other plant extracts have been proposed and tested in clinical trials.…”
Section: Discussionmentioning
confidence: 99%